2020
DOI: 10.1371/journal.pone.0235982
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk and associated factors of healthcare waste in selected hospitals of Kathmandu, Nepal

Abstract: Background Healthcare waste management is the subject of a neglected issue in many developing countries. Health care facilities are facing a major challenge in handling healthcare wastes and reducing their potential risks to human health and the environment. Insufficient understanding of the risk associated with healthcare waste by health workforce can contribute to poor waste management practices. The main aim of this study is to assess risk perception towards healthcare waste among hospital atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…Practical training on waste management practices is essential in developing people's knowledge and attitudes. This finding is revealed by Gizalew et al [36], Dewi [37], Wafula et al [38], and Karkil et al [50].…”
Section: Practical Trainingsupporting
confidence: 54%
“…Practical training on waste management practices is essential in developing people's knowledge and attitudes. This finding is revealed by Gizalew et al [36], Dewi [37], Wafula et al [38], and Karkil et al [50].…”
Section: Practical Trainingsupporting
confidence: 54%
“…Lack of awareness about the health hazards of HCW, inadequate training in proper waste management, and the absence of waste management and disposal systems, insufficient financial and human resources, and the low priority given to the topic are the most common problems associated with poor HCWM practice 6 39–42. The capacity of a healthcare facility to effectively manage HCW is influenced by a variety of factors, such as staff commitment and work experience, knowledge and training, the presence of waste management utilities, a committed waste management team and a national regulatory framework 29 41 43 44…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have stated that the main cause of anemia in Indonesia is a lack of knowledge about anemia which results in a high rate of anemia. Therefore, it is necessary to carry out educational activities regarding anemia, the dangers of anemia and prevention so that the prevalence of anemia among adolescent girls can be suppressed [10]. One of the causes of the high prevalence rate of anemia is the unhealthy diet of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not mean that some departments are not related to the risk of disease from hazardous health-care waste. Previous research found that housekeeping department was more at risk to be infected with disease from health-care waste [10]. Knowledge is crucial in proper waste management, particularly the knowledge to protect one's self from hazardous health-care waste.…”
Section: Discussionmentioning
confidence: 99%